2001
DOI: 10.1097/00000539-200107000-00016
|View full text |Cite
|
Sign up to set email alerts
|

The Dose-Response Relationship for Clonidine Added to a Postoperative Continuous Epidural Infusion of Ropivacaine in Children

Abstract: The addition of clonidine (0.08-0.12 microg.kg(-1).h(-1))to a continuous epidural infusion of ropivacaine was found to improve postoperative pain relief in children. No clinically significant signs of sedation or other side effects were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 26 publications
1
32
1
2
Order By: Relevance
“…Post-operative complication i.e. nausea, vomiting are less in epidural clonidine group than epidural fentanyl which coincides with the study of Topcu I et al [21] Pruritis is more with epidural fentanyl group than epidural clonidine group which coincides with the findings of Sinatra RS et el, Halonen DM et al [22] In the present study epidural bupivacaineclonidine group found to be devoid of any marked side effects compared to bupivacaine-fentanyl group which coincides with the studies of Constant I et al, Negri PD et al, Cucchiaro et al [20,23,24] …”
Section: Section: Anaesthesiasupporting
confidence: 91%
“…Post-operative complication i.e. nausea, vomiting are less in epidural clonidine group than epidural fentanyl which coincides with the study of Topcu I et al [21] Pruritis is more with epidural fentanyl group than epidural clonidine group which coincides with the findings of Sinatra RS et el, Halonen DM et al [22] In the present study epidural bupivacaineclonidine group found to be devoid of any marked side effects compared to bupivacaine-fentanyl group which coincides with the studies of Constant I et al, Negri PD et al, Cucchiaro et al [20,23,24] …”
Section: Section: Anaesthesiasupporting
confidence: 91%
“…18 Epidural adjuvants, such as clonidine (0.08-0.12 lgÁkg -1Áhr -1 ) added to a continuous epidural infusion of 0.08% ropivacaine (0.16 mgÁkg -1 Áhr -1 ), reduce the required dose of anesthetic and enhance analgesia. 19 A local anesthetic-opioid combination is also effective. For example, a double-blind randomized comparison of three solutions administered by continuous epidural infusion (15 mLÁhr -1 ) for postoperative analgesia (0.125% bupivacaine in 0.9% saline, diamorphine in 0.9% saline [0.5 mg in 15 mL], ordiamorphine mixed with 0.125% bupivacaine) was shown to be superior to each modality alone, yielding better pain relief with fewer adverse effects following major gynecological surgery.…”
Section: Developmentsmentioning
confidence: 99%
“…We used a relatively high dose of clonidine (up to 0.75lg/ kg/h) compared with previously published studies that added epidural clonidine to local anaesthetic agents. 7,9,13 This was based on our institutional practice that took into account the specific problems of postoperative pain and muscle spasm in children with CP undergoing SEMLS and evidence that higher doses of clonidine could be beneficial. Analgesia is enhanced with increasing dose.…”
Section: Discussionmentioning
confidence: 99%
“…6 The use of epidural clonidine has several potential benefits. It enhances and prolongs the sensory nerve block of local anaesthetics 7 and produces fewer side effects than epidural morphine 8 or fentanyl. 9,10 In addition, clonidine has anti-spasm properties 11 and little respiratory depressant effect.…”
mentioning
confidence: 99%